An economic evaluation of different sinus lift techniques - Listl, Stefan; Faggion Junior, Clóvis Mariano (Journal of clinical periodontology, 2010)
To identify the most cost-effective approach to sinus lifting on the basis of currently available evidence.
Gesehen am 28.03.2023